Detection and Role of Some Interleukins and Tumor Necrotic Factor Alpha among Patients with Tuberculosis - Wael Rasheed Obaead Alfatlawi; Marwa Kadhim Khudhair; Jwan Ahmed Ali (Medical Journal of Babylon)
Background: The bacterium Mycobacterium tuberculosis causes tuberculosis (TB), a contagious illness. Primarily, it affects the respiratory system, although it may also influence other parts of the body (known as extrapulmonary TB). Objective: This study aims to measure the levels of IL-2, IL-10, IL-17, and TNF-α in patients infected with TB and determine the influence of these cytokines on the confirmed infection. Materials and Methods: This study is limited to 40 collected samples from individuals diagnosed with TB. The selected samples ranged between (20–70) years of age, in addition to the other 40 who are apparently healthy as a control group within the same age range. The studied samples were collected between February 2020 and February 2021 from the Babylon Center for Tuberculosis and Chest Disease. Serum was used to estimate the levels of IL-2, IL-10, IL-17, and TNF-α using a sandwich ELISA experiment. Results: The results revealed a highly significant increase in IL-2 levels 83.88 ± 10.62 ng/L in TB patients compared to healthy individuals 58.22 ± 3.12 ng/L, The IL-10 levels showed highly significant differences between the tested subjects (P > 0.05). The mean IL-17 level was increased in TB patients to 115.14 ± 7.99 ng/L, whereas it decreased to 80.00 ± 7.07 ng/L in healthy individuals, and the serum TNF-α concentration was increased in TB patients to 1.33 ± 0.28 ng/L compared to healthy individuals at 0.515 ± 0.07 ng/L. Conclusions: IL-2, IL-10, and IL-17 were significant components of the immune response to TB; their distinct profiles, obtained from easily accessible kits, might be used to diagnose TB cases. TNF-α is a significant contributor to both the prevention and progression of TB.